ANALISIS PENGARUH STRES KERJA,BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN CV ANUGERAH PERKASA - MUHAMMAD ALI YAFI (Jurnal Manajerial, 2018)
This study aims to determine and analyze the effect of partial and simultaneous analysis of the effect of work stress, organizational culture, work motivation, on employee performance CV. Anugerah Perkasa. Sampling was carried out by Saturated Sampling technique by distributing questionnaires as many as 40 respondents. The analytical tool used is to use multiple linear regression with the help of SPSS / Windows. V.20. Hypothesis testing using t test and F test, with a significant level of 5%. The calculation results show that the three variables included in the analysis together have a significant influence on the performance of CV. Anugerah Perkasa. This conclusion is based on the results of calculations that show a calculated F value of 8,322 more than F table 2,839. The three variables, it turns out the results obtained t count (2.388)> t table (2.0281) at a significant level of 2.5%. means work stress affects employee performance at CV. Anugerah Perkasa. And Organizational Culture results tcount (2.704)> t table (2.0211) at a significant level of 2.5%. Then it can be interpreted that organizational culture influences employee performance at CV. Anugerah Perkasa. Then Work Motivation results tcount (3,327)> t table (2,0211) at a significant level of 2.5%. Then it can be interpreted that work motivation partially affects the performance of employees at CV. Anugerah Perkasa. So the entire independent variable (work stress, organizational culture, and work motivation) is very influential on the dependent variable (employee performance)